2004
DOI: 10.1093/nar/gnh135
|View full text |Cite
|
Sign up to set email alerts
|

Protein evolution by codon-based random deletions

Abstract: A method to delete in-phase codons throughout a defined target region of a gene has been developed. This approach, named the codon-based random deletion (COBARDE) method, is able to delete complete codons in a random and combinatorial mode. Robustness, automation and fine-tuning of the mutagenesis rate are essential characteristics of the method, which is based on the assembly of oligonucleotides and on the use of two transient orthogonal protecting groups during the chemical synthesis. The performance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…9a, which is published as supporting information on the PNAS web site). Several tolerated short deletions and insertions in the ⍀-loop have been described, some of which result in altered substrate specificity (17,18).…”
Section: Resultsmentioning
confidence: 99%
“…9a, which is published as supporting information on the PNAS web site). Several tolerated short deletions and insertions in the ⍀-loop have been described, some of which result in altered substrate specificity (17,18).…”
Section: Resultsmentioning
confidence: 99%
“…Although the three other motifs SXXK, SDN, and K(S/T)G are conserved, the absence of Glu 166 suggested that these proteins are rather PBPs than ␤-lactamases. Although substitutions in the ⍀-loop can occur naturally, giving rise to extended spectrum lactamases (25), insertions or deletions were mainly genetically engineered in this region (26,27). Only one example of a natural duplication in the ⍀-loop of a class A ␤-lactamase has been reported (28).…”
Section: Resultsmentioning
confidence: 99%
“…Recent developments in protein engineering have proposed random amino acid deletions as a good alternative to classic amino acid substitution mutagenesis to expand protein sequence space [Osuna et al, 2004;Raghunathan et al, 2012]. Here we presented evidence that codon deletion is a feasible approach with which to enhance SD accessibility and protein expression.…”
Section: Discussionmentioning
confidence: 80%
“…In our previous work, we used an oligonucleotide library assembled by the Codon-Based Random Deletion (COBARDE) mutagenesis approach [Osuna et al, 2004] and successfully isolated two functional deletion mutants, sgGFPΔI128 and sgGFPΔD129, which remained robustly fluorescent under direct visualization with sunlight. In fact, E. coli cells expressing sgGFPΔD129 at 37 ° C were slightly less fluorescent than were those expressing the parental protein sgGFP and were more fluorescent at 30 ° C. A similar result was obtained by Liu et al [2015] for several internal deletion mutants of GFPuv, the relative fluorescence of which was improved at a lower temperature.…”
Section: Discussionmentioning
confidence: 99%